FOREIGN LANGUAGE TEACHING METHODOLOGY IN THE 21ST CENTURY: INNOVATIVE METHODS - Shermamatova , Zaynab Azimjonovna; Abduraimova , Mohichehra Yusup qizi; Bozorova , Husnora Bahrillo qizi (Educational Research in Universal Sciences, 2023)
The article explores diverse approaches to English language instruction, emphasizing the adoption of innovative techniques for enhancing students’ English communication skills. Emerging methods, including group discussions, role-playing, and brainstorming, contribute to boosting students’ confidence in using English.